2001
DOI: 10.1093/jac/47.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Acridine--a neglected antibacterial chromophore

Abstract: The use of acridines as antimicrobial agents was first proposed by Ehrlich and Benda in 1912, and the first clinical use of these agents occurred in 1917. Many compounds containing the acridine chromophore were synthesized and tested, and the aminoacridines found wide use, both as antibacterial agents and as antimalarials, during World War II. The emergence of the penicillins eclipsed the acridines in antisepsis due to the greater therapeutic efficacies of the former. However, with the current massive increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
146
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(151 citation statements)
references
References 56 publications
1
146
0
4
Order By: Relevance
“…The HIF-2␣ PAS-B crystal structure was shown to contain an internal cavity, which accommodated a small molecule that partially disrupted the heterodimerization of isolated HIF-2␣ and HIF-1␤ PAS subdomains in vitro but was not reported to have any effect on heterodimerization of the full length proteins or on HIF-1 transcriptional activity (13). We show that ACF binds to the PAS-B subdomain of HIF-1␣ or HIF-2␣, thereby blocking het- ACF has known trypanocidal, antibacterial, and antiviral activities (14). Effects of ACF on cancer cells were first reported 50 years ago (15).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The HIF-2␣ PAS-B crystal structure was shown to contain an internal cavity, which accommodated a small molecule that partially disrupted the heterodimerization of isolated HIF-2␣ and HIF-1␤ PAS subdomains in vitro but was not reported to have any effect on heterodimerization of the full length proteins or on HIF-1 transcriptional activity (13). We show that ACF binds to the PAS-B subdomain of HIF-1␣ or HIF-2␣, thereby blocking het- ACF has known trypanocidal, antibacterial, and antiviral activities (14). Effects of ACF on cancer cells were first reported 50 years ago (15).…”
Section: Discussionmentioning
confidence: 85%
“…Unlike other drugs that indirectly inhibit HIF-1 activity, ACF binds directly to both HIF-1␣ and HIF-2␣. ACF has been administered to patients for at least 5 months without major side effects (14), suggesting that it may be a candidate for clinical trials. ACF can also serve as the lead compound for development of drugs to treat patients with cancer subtypes in which increased HIF-1␣ or HIF-2␣ levels are associated with disease progression and patient mortality (2,5).…”
Section: Discussionmentioning
confidence: 99%
“…9AA was initially identified as an antibacterial agent (42,47). Subsequently, it was found that staining of histopathological sections with 9AA could be used to locate malignant cells in many tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The 1,8-acridinediones and their derivatives are known to exhibit a wide range of biological and pharmaceutical properties such as antibacterial, 1 antimicrobial, 2 anticancer, [3][4][5] antitumor, [6][7] antifungal, 8 antimalarial, 9 antiviral, 10 larvicidal 11 and hypertensive 12 activities. Electroluminescent devices based on decahydroacridinedione (DAD) derivatives exhibit good efficiencies and excellent color purity.…”
Section: Introductionmentioning
confidence: 99%